Enhancing Students’ Self-Reflection with 360° VR Video Across Digital Literacy Levels - Muhammad Rais; Kurnia Prima Putra; Marhayati Marhayati; Andi Baso Kaswar (International Journal of Pedagogy and Teacher Education, 2026)
Microteaching is central to the development of pre-service teachers’ instructional skills, yet conventional two-dimensional video often fails to capture the spatial and interactive complexity of classroom teaching, resulting in relatively superficial reflection. This study aimed to examine whether 360° Virtual Reality (VR) video was associated with higher self-reflection outcomes than PPT-based video and whether these differences varied across digital literacy levels. A quasi-experimental 2 × 2 factorial design was employed with 67 fourth-semester undergraduates from the Agricultural Technology Education program at Universitas Negeri Makassar. Participants were assigned to an experimental group (n = 32) using 360° VR video and a control group (n = 35) using PPT-based video, while digital literacy was classified as high (n = 38) or low (n = 29). Post-test self-reflection scores were analysed using two-way ANOVA, with pre-test data used for baseline comparison. The results showed significant main effects of learning media and digital literacy. Students using 360° VR video achieved higher self-reflection scores (M = 77.23) than those using PPT-based video (M = 74.73; F = 74.776, p < .001), and students with high digital literacy outperformed those with low digital literacy (F = 8.950, p = .004). A significant interaction effect was also found (F = 13.457, p = .001), indicating that the advantage of 360° VR video was greater among students with higher digital literacy. These findings suggest that 360° VR video, particularly when paired with stronger digital literacy, may better support self-reflection in microteaching and strengthen reflective practice in teacher education.